Kecemasan Akademik dalam Perspektif Mahasiswa Muslim - Khadijah Al Fatih Rachmat; Muhammad Faqih Aziz; Syalwah Fadiah Innayah; Yuminah Rahmatullah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine academic anxiety from the perspective of Muslim students. Using a descriptive qualitative approach, data were collected through semi-structured interviews with five Muslim students from various universities in Jakarta and its surroundings. The results of the study revealed that academic anxiety is influenced by internal and external factors, such as high grade demands, parental pressure, and fear of failure. Islamic values such as tawakal, patience, and ikhtiar are effective coping mechanisms in managing this anxiety. Religious activities, including prayer, supplication, dhikr, and reading the Qur'an, play an important role in calming the mind and strengthening students' emotional resilience. These findings emphasize the importance of integrating spiritual values into strategies for managing academic anxiety for Muslim students.